Integrated Geophysical Analyses of Shallow-Water Seismic Imaging With Scholte Wave Inversion: The Northern Adriatic Sea Case Study - Giustiniani, M.; Tinivella, U.; Parolai, S.; Donda, F.; Brancolini, G.; Volpi, V. (Frontiers in Earth Science, 2020)
The integrated analysis of different seismic wave types on a record is a very useful approach for a comprehensive characterization of marine sediments, especially in shallow water environments. The proposed integrated method to analyze seismic data in post-critical condition consists of: 1) the inversion of Scholte waves to obtain a reliable Vs distribution of the near-surface; 2) pre-processing of seismic data; 3) construction of the P-wave velocity field by using all available information, including available well data; and 4) the application of the wave equation datuming and post-processing, such as pre-stack time migration. We demonstrate how this approach could be successfully applied on seismic datasets characterized by post-critical conditions and the occurrence of the Scholte waves, which may be exploited to provide fundamental information instead of being only an unwanted effect. In conclusion, the integrated analysis of seismic events can help with data processing by providing better seismic imaging, which is a priority for reliable seismostratigraphic interpretation.